Model Evaluasi Kinerja Pustakawan Sebagai Dasar Pengembangan Profesionalisme Pustakawan di PTKIN - Sulaiman Sulaiman; Suprapto Suprapto (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2019)
The research aims to (1) Evaluate librarians' competencies, especially within PTKIN. (2) Formulate a librarian competency development program at PTKIN. Research is evaluation research. The research used kuisioner as instrument to measure self-evaluating librarian competencies. Based on the literature review, librarian self-evaluation indicators are self-concept, work motivation and librarian performance. Self-concept is measured through 17 questions, work motivation is measured through 7 questions and librarian's performance is measured through 47 questions. The Research is done at Sunan Ampel Surabaya UIN, Malang Sunan Malik Ibrahim UIN, Kediri IAIN, Tulungagung IAIN and Ponorogo IAIN. The results of the librarian's self-evaluation showed that the librarians with very positive self-concept were 41% and the positive self-concept was 59%. Librarians who have very high motivation are 41%, high motivation is 41%, low motivation is 15% and motivation is very low 2%. Librarians who have low performance are 2.2%, moderate performers are 32.6%, high performers are 37%, and very high performers are 28.3%. The performance of librarians who are still weak is information technology literacy, conducting library research and writing scientific papers and publishing them in scientific journals / forums.